2013
DOI: 10.1037/a0032088
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mental health care use among male and female veterans deployed in support of the wars in Afghanistan and Iraq.

Abstract: What factors predict whether Operation Enduring Freedom and Operation Iraqi Freedom (OEF/OIF) veterans who need mental health care receive that care? The present research examined factors associated with a need for care, sociodemographic characteristics, deployment experiences, and perceptions of care as gender-specific predictors of overall mental health care use and Veterans Affairs (VA) mental health care use for male and female OEF/OIF veterans (N = 1,040). Only veterans with a probable need for mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 34 publications
7
45
1
Order By: Relevance
“…Contrary to our hypothesis that suicidal individuals receiving the intervention would seek mental health treatment most frequently, no significant difference in treatment seeking behaviors was found between the intervention and control groups for suicidal participants. Our findings support previous research that greater symptom severity predicts treatment utilization (Di Leone et al, 2013; Elbogen et al, 2013; Haskell et al, 2011). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Contrary to our hypothesis that suicidal individuals receiving the intervention would seek mental health treatment most frequently, no significant difference in treatment seeking behaviors was found between the intervention and control groups for suicidal participants. Our findings support previous research that greater symptom severity predicts treatment utilization (Di Leone et al, 2013; Elbogen et al, 2013; Haskell et al, 2011). …”
Section: Discussionsupporting
confidence: 91%
“…Suicidal ideation significantly increases the risk of suicide attempts and eventual death by suicide (Kessler et al, 2005). It is noteworthy that greater mental health symptom severity predicts increased use of VHA services among OEF/OIF Veterans (Di Leone et al, 2013; Elbogen et al, 2013; Haskell et al, 2011). In a study of 1,388 OEF/OIF Veterans, 69% with PTSD and 67% with depression reported past year psychiatric treatment (Elbogen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated, the variables representing need for care, including decreased rating of one’s health and increased level of disability, both predicted increases in help seeking as expected based on previous research 12 . The enabling factors in this study, including income and distance to closest VA, were also significant predictors of service use.…”
Section: Discussionsupporting
confidence: 70%
“…This study also found that need-based variables were the most significant predictors of utilization. Although the model has not been formally tested in OIF-OEF veterans, a recent study of mental health care utilization in returning veterans found that probable need for services, income, combat exposure, and perceptions of VA care were significantly related to use 12 .…”
mentioning
confidence: 99%